2016
DOI: 10.12944/cwe.11.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Runoff for Ozat Catchment using RS and GIS Based SCS-CN Method

Abstract: Estimation of runoff in a watershed is a prerequisite for design of hydraulic structures, reservoir operation and for soil erosion control measures. Water resource planning and management is important and critical issue in arid and semi-arid regions. Runoff from a watershed affected by several geo-morphological parameters and for a particular watershed land use change can affect the runoff volume and runoff rate significantly. Several methods are investigated to estimate the surface runoff from a catchment but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Köylü and Geymen [21] applied SCS-CN method to calculate the runoff in the catchment basin of the Yamula Dam (Kızılırmak River of Turkey) and found SCS-CN method is sensitive to LULC change and change of CN (change of the runoff values). Chavda et al [9] implemented SCS-CN method for estimation of surface runoff and water availability for two sites in Junagadh, Gujarat and suggested surface water harvesting structures. Topno et al [63], also computed annual runoff depth for ungauged catchment area (Vindhyachal region) and revealed that the SCS-CN method can be used to estimate surface runoff depth when adequate hydrological information is not available.…”
Section: Introductionmentioning
confidence: 99%
“…Köylü and Geymen [21] applied SCS-CN method to calculate the runoff in the catchment basin of the Yamula Dam (Kızılırmak River of Turkey) and found SCS-CN method is sensitive to LULC change and change of CN (change of the runoff values). Chavda et al [9] implemented SCS-CN method for estimation of surface runoff and water availability for two sites in Junagadh, Gujarat and suggested surface water harvesting structures. Topno et al [63], also computed annual runoff depth for ungauged catchment area (Vindhyachal region) and revealed that the SCS-CN method can be used to estimate surface runoff depth when adequate hydrological information is not available.…”
Section: Introductionmentioning
confidence: 99%
“…A number of models are mentioned in the literature which are modelling rainfall-runoff process in a basin using SCS-CN method in a gauged basin 17 . Using the climate change projections 18 , one can use such models for predicting the behaviours of river flows.…”
Section: Contribution Of Ungauged Tributaries Falling Directly Into T...mentioning
confidence: 99%